Seismic performance of corroded reinforced concrete column-slab connections - Sutantyo, Samuel Kurniawan (Nanyang Technological University, 2021)
This final year project investigated the effect of steel reinforcement corrosion towards the behaviour of reinforced concrete (RC) Flat Plate Slab-Column connections subjected to reversed cyclic loading. Flat plate RC system has been used predominantly around the world due to the ease and speed of making the formwork. Aside from that, beams and drop panel are also omitted, which permits the higher floor to floor height. Flat plates, however, do come with some disadvantages of its own. Due to the lack of any shear reinforcement and drop panel, the slab-column connection is susceptible punching failure, especially when the building is also subjected to earthquake loadings. The condition is further worsened by corrosion of rebars inside the concrete, which effectively reduces the ultimate strength capacity of the connections. Thus, in this report, analytical investigations and simulations were conducted to observe the effect of corrosions on the ultimate strength and drift capacity of slab-column connections under simulated seismic loadings. To simulate the behaviour of RC slab column connections under the loadings, non-linear Finite Element Analysis using DIANA 9.44 was used. Total strain rotate crack model was applied to design the RC joints. To ensure the accuracy of the simulation software, several validations were made using non-corroded slab column joints from various papers. Parametric study was done to observe the influence of different parameters. These parameters include corrosion levels, axial force ratio, slab reinforcement ratio, and slab thickness. The results obtained would then be used to propose an equation to predict the ultimate strength of corroded slab-column joints.